Analysis of Academic Characteristics of USK FMIPA Undergraduate Students Using the Chaid Method - AR, Fitriana (Syiah Kuala University, 2023)
The purpose of this research is to find out the most significant factors to the students study period, to divide the data into smaller groups based on the relationship between the response variables ande the explanatory variables. The characteristics and educational background are gender, school origin, major, supervisors level of education, Grade Point Average (GPA), and trial grades. The method displays a graphical tree structure in the form of a diagram that explains the relationship between categorical response variables and categorical explanatory variables so that it is easy to interpret. The test used to produce a tree diagram is the Chi-square test and Bonferroni correction. In this study, data were used on graduates of the faculty of Mathematics and Natural Sciences USK class of 2017 who graduated from september 2020 to August 2022. The result of the study showed that the most significant factors for the period of study were GPA, school origin, supervisor education,level, type gender, and major. In terms of classification accuracy, the percentage accuracy of the model correctly classifying the study period is 71,8%.